Formation development and evolution of oral fast disintegrating film of zolmitriptan - N, Surya Naik; Marabathuni, V Jhansi Priya; Narapusetty , Naidu (International Journal of Indigenous Herbs and Drugs, 2022)
The main aim of the present study was to develop oral fast disintegrating film of Zolmitriptan for the treatment of migraine. Oral fast disintegrating films were prepared by HPMC E5 as a polymer, ipropylene iglycol ias an iplasticizer, isodium istarch iglycolate is a super disintegrant, and aspartame it is a sweetener. optimization was done by using the i23 factorial design. iThe optimized batch was prepared by using i4% of HPMC iE5, i1.5 i% of ipropylene iglycol, and i4% of isodium istarch iglycolate. It gave disintegration time I of I 9 sec, drug release of i98.15%, and folding endurance of i200 times. from the above research work it is concluded that oral fast disintegrating film of Zolmitriptan was successfully designed and developed by solvent casting method and it gives quick onset of action, patient compliance